Determinan internal dan external dari profitabilitas Bank Perkreditan Rakyat - Ponziani, Regi Muzio (Jurnal Akuntansi, Manajemen dan Ekonomi, 2022)
This research aims to investigate how internal and external factor influence the rate of profitability of rural banks in Indonesia. Internal factors are factors within the bank itself, namely core capital, loan to deposit ratio, and nonperforming loan ratio. External factors are macroeconomics variables uncontrollable to the rural banks, such as inflation and interest rate. VECM test proved the existence of cointegration function. Any deviation from last period will be adjusted at the rate of 8.863%. In the long-run, core capital and inflation affect rural banks’ performance. Impulse response function indicated that any shocks that occurred to core capital, inflation, loan to deposit ratio and nonperforming loan had the inhibiting effect on rural banks’ performance. On the other hand, interest rate was the only variable that provided positive stimulus on rural banks’ performance. This showed us that rural banks should have improved risk and capital management practice so that they will not have to depend on the interest rate to have a better performance.